Coconut (Cocos nucifera L.) Processing Training to Become Virgin Coconut Oil (VCO) to Improve the Economy and Community Health in Setiawaras Village, Cibalong District, Tasikmalaya Regency - Rudi Priyadi; Yaya Sunarya; Rina Nuryati; Ade Hilman Juhaeni; Septian Cahya Azhari (LPPM UIKA Bogor, 2022)
The potential of coconut in Setiawaras Village, Cibalong District, Tasikmalaya Regency is very abundant. In general, people only sell coconut directly to collectors whose selling price is relatively small. The knowledge of the people who are still simple causes the optimization of the potential of coconut not to be processed optimally. Optimizing the potential of coconut in Setiawaras Village can be an alternative way to encourage the creation of a strong economy in the community. This community service activity aims to provide training on the manufacture of virgin coconut oil (VCO). The first method used in community service is counseling and the second is training. Counseling serves as a means to introduce and explain to the public the potential of coconut that exists in the community and provide an understanding of processing coconut into virgin coconut oil (VCO) which has higher benefits from a health and economic perspective. Furthermore, training activities were carried out to provide skills to the community in processing coconut into virgin coconut oil (VCO). The method of making VCO oil is done by a fermentation system using probiotics Saccharomyces sp and Lactobacillus sp. simple so that people can understand and do it. The targets of this community service activity are farmer groups and the Family Welfare Empowerment Women (PKK) group.